Nondrug Treatment Approaches Used in Alcohol and Substance Addictions and Related Factors. (December 2021) - Turan, Caglar; Yazici, Esra; Yazici, Ahmet B.; Erol, Atila
Abstract : Objectives: Current treatment methods in alcohol and substance use disorders (ASUDs) cannot meet the demands of patients for many reasons. This situation may result in individuals with addiction seeking different approaches. This study aims to investigate nondrug methods used by individuals with ASUD to cope with their disorder and the factors that may be associated with it. Materials and Methods: The study was carried out on 103 volunteer patients who presented to a Training and Research Hospital alcohol substance treatment center. In the study, the God Attachment Inventory, the Addiction Profile Index-Practitioner Form, and the Non-Drug Treatment Questionnaire were used, and Structured Clinical Interview for DSM-IV (SCID-1) and Structured Clinical Interview for DSM-IV (SCID-2) psychiatric interviews were conducted. Result: In individuals with addiction, the rate of seeking any nondrug method was found to be 33%. To get rid of addiction, turning to religion was mostly preferred (24.3%). In terms of subheadings, self-help methods such as praying (17.4%) and engaging in sports (6.7%) were the most preferred. No relationship was found between the patients' attachment style to God and personality disorder diagnoses and the frequency of seeking nondrug methods and the type of nondrug method. It has been found that there is a relationship between the severity of addiction and the use of nondrug methods. Conclusions: In addition to the medical approaches of patients with ASUD problems, it is observed that they attempt to cope using traditional and complementary methods and prefer the self-help methods among these methods. However, further studies are needed to investigate the contribution of these methods to current treatment methods.